Structural heterogeneity promotes triggered activity, reflection and arrhythmogenesis in cardiomyocyte monolayers - Auerbach, David S (Blackwell Science Inc, 2011)
ABSTRACT: Patients with structural heart disease are predisposed to arrhythmias by incompletely understood mechanisms. We hypothesized that tissue expansions promote source-to-sink mismatch leading to early after-depolarizations (EADs) and reflection of impulses in monolayers of well-polarized neonatal rat ventricular cardiomyocytes. We traced electrical propagation optically in patterned monolayers consisting of two wide regions connected by a thin isthmus. Structural heterogeneities provided a substrate for EADs, retrograde propagation along the same pathway (reflection) and reentry initiation. Reflection always originated during the action potential (AP) plateau at the distal expansion. To determine whether increased sodium current (I(Na)) would promote EADs, we employed adenoviral transfer of Nav1.5 (Ad-Nav1.5). Compared with uninfected and adenoviral expression of green fluorescent protein (Ad-GFP; viral control), Ad-Nav1.5 significantly increased Nav1.5 protein expression, peak and persistent I(Na) density, AP upstroke velocity, AP duration, conduction velocity and EAD incidence, as well as reflection incidence (29.2%, n = 48 vs. uninfected, 9.4%, n = 64; and Ad-GFP, 4.8%, n = 21). Likewise, the persistent I(Na) agonist veratridine (0.05–3 μm) prolonged the AP, leading to EADs and reflection. Reflection led to functional reentry distally and bigeminal and trigeminal rhythms proximally. Reflection was rare in the absence of structural heterogeneities. Computer simulations demonstrated the importance of persistent I(Na) in triggering reflection and predicted that the gradient between the depolarizing cells at the distal expansion and the repolarizing cells within the isthmus enabled retrograde flow of depolarizing electrotonic current to trigger EADs and reflection. A combination of a substrate (structural heterogeneity) and a trigger (increased persistent I(Na) and EADs) promotes reflection and arrhythmogenesis.